Relacje polsko-niemieckie piórem malarza spisane na podstawie Pamiętników Juliana Fałata (1935) i Wspomnień Wojciecha Kossaka (1913/1973) - Krauze-Pierz, Justyna M. (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
This article is an analysis of two autobiographical texts by famous Polish painters of the turn of the century: Julian Fałat’s Pamiętniki (Diaries) from 1935 and Wojciech Kossak’s Wspomnienia (Reminiscences) from 1913. These texts constitute a source of information not only about the life of Polish artists at the imperial court in Berlin, but also a treasury of historical knowledge about the moods prevailing in the Wilhelmine era, the Polish–German relations in particular. In both texts, the most important figure is that of the German emperor, his involvement in the affairs of art and concern for the fate of outstanding Polish painters. The analysed texts allowed, above all, for showing the difficulties in Polish–German relations at the turn of the century, the ambivalence of the German emperor in relation to the Polish issue and individual Poles, and the difficulties of Polish artists in maintaining the balance between being the court painter of the German emperor and a Polish patriot.